How does head position affect laryngeal vision with a video laryngeal mask airway? - Caridad G. Castillo-Monzón; Hugo Antonio Marroquín-Valz; Tomasz Gaszynski; Manuel Cayuela; Javier Orozco; Pawel Ratajczyk (Frontiers in Medicine)
BackgroundThe Laryngeal Mask Airway Vision Mask (LMA VM) is a supraglottic airway device (SAD) with a vision guidance system. The ideal head and neck position for direct laryngoscopy is known, but the ideal position for placing a LMA is not. The objective of this study is to evaluate and compare the optimal position for placement of a video laryngeal mask airway.MethodsThis prospective, observational, transversal, and analytical study was performed in 72 consecutive patients. In the same patient, laryngeal vision was first assessed with the head and neck in the sniffing position and then with the head in the neutral position. Procedures were performed by the same investigator. The assessment of the laryngeal view was performed using two classifications: Cormack–Lehane classification and Brimacombe classification. The placement of the device was considered adequate when the Cormack–Lehane rating was between 1 and 2 and the Brimacombe rating between 2 and 4.ResultsIn this study, 72 patients participated. In the assessment of the glottis using the Cormack-Lehane classification for fibre-optic view, laryngeal visibility was adequate in 64 (88.89%) patients in the neutral position and in 65 (90, 28%) patients in the sniffing position (p > 0.05). In the fibre-optic view of the glottis, evaluated using the Brimacombe classification, laryngeal visibility was adequate in 68 (93%) patients in the neutral position and in 69 (95%) patients in the sniffing position (p > 0.05). There was no statistically significant difference in the rate of success between the sniffing position (70 patients, 97.22% success rate) and the neutral position (67 patients, 93.06% success rate) during the first insertion attempt. Two patients required a second attempt in the sniffing position, while five patients required a second attempt in the neutral position.ConclusionAn adequate sniffing position did not result in a better glottic view than the neutral position. Additional manoeuvres were equal in both positions. The head–neck position does not influence on the placement of a third-generation SAD.